Agnostycyzm uczonych – wybrane postacie - Drozdowicz, Zbigniew (My University, 2020)
In these remarks I do undertake one more time the attempt to answer the fol- lowing question: what do agnostics really want? This issue is so complicated that even the agnostics themselves had great trouble in delivering the answer. This is also related to these agnostics, such as the recalled here Charles Darwin, Albert Einstein, and Stephen W. Hawking, who belong to the greatest format of scholars. The agnostics are being distanced from, both the atheists and theists. However they do judge differently their views it is important that as well the first as the latter ones may appreciate what stands behind agnosticism and this might be very variable.
Keywords: agnostycyzm; Charles Darwin; Albert Einstein; Stephen Hawking; opposition to theism and atheism